Martensitic stainless steel material, its manufacturing method, and slide member

JP7640237B2Active Publication Date: 2025-03-05NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020132642
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-04
Publication Date
2025-03-05
Estimated Expiration
2040-08-04

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、耐腐食摩耗性に優れるマルテンサイト系ステンレス鋼材及びその製造方法、並びに摺動部材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640237000001
    Figure 0007640237000001
  • Figure 0007640237000002
    Figure 0007640237000002
  • Figure 0007640237000003
    Figure 0007640237000003
Patent Text Reader

Abstract

To provide a martensitic stainless steel having excellent anticorrosive wear resistance.SOLUTION: A martensitic stainless steel has a composition comprising C: 0.28-0.70 mass%, Si: 2.0 mass% or less, Mn: 2.0 mass% or less, Cr: 10-17 mass%, Mo: 3.0 mass% or less, N: 0.008-0.40 mass%, Ti: 0.1 mass% or less, Nb: 0.5 mass% or less, V: 1.0 mass% or less, and W: 1.0 mass% or less, the total content of Nb, V and W being 0.1-2.0 mass%, with the balance being Fe and impurities. The martensitic stainless steel has a metallographic structure comprising a carbonitride that comprises 25 mass% or less of Cr, the total content of Nb, V and W being 10 mass% or more, with an average particle size of 5.0 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a martensitic stainless steel material, a manufacturing method thereof, and a slide member. [Background technology]

[0002] Sliding members such as bearings are components that support the shafts of components that rotate or reciprocate, and are widely used in various fields. For example, in automobiles and industrial machines, rolling bearings are generally used to support the rotating shafts of components. In high-pressure pumps and injectors, retaining members are generally used to support reciprocating shafts.

[0003] Depending on the application, sliding members may be used in environments where corrosion is likely to occur, and therefore need to be made of materials suitable for the environment in which they are used. For example, Patent Document 1 proposes the use of steel containing 0.60-0.95 wt% C, 10.0-13.0 wt% Cr, 0.2-1.5 wt% Si, and 0.2-1.0 wt% Mn, with at least one of 0.5-2.0 wt% Mo and 0.5-2.0 wt% V added to disperse and precipitate fine Mo- or V-based carbides of 50-300 nm, with the remainder being Fe and unavoidable impurities, as a material for bearings used in environments where foreign matter or muddy water is likely to be mixed in. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 4441947 Summary of the Invention [Problem to be solved by the invention]

[0005] However, conventional materials used for sliding members have a problem that they are susceptible to corrosion and wear when used in a salty environment, shortening the lifespan of the sliding members. Therefore, there has been a demand for the development of a material for sliding members that can be suitably used in various environments, including salty environments.

[0006] The present invention has been made to solve the above-mentioned problems, and has an object to provide a martensitic stainless steel material having excellent corrosion and wear resistance, a manufacturing method thereof, and a slide member. [Means for solving the problem]

[0007] As a result of intensive research focusing on martensitic stainless steel materials, the inventors have found that the above problems can be solved by controlling the composition, and the components and average grain size of carbonitrides contained in the metal structure, and have thus completed the present invention.

[0008] That is, the present invention provides a composition comprising: 0.28 to 0.70 mass% C, 2.0 mass% or less Si, 2.0 mass% or less Mn, 10 to 17 mass% Cr, 3.0 mass% or less Mo, 0.008 to 0.40 mass% N, 0.1 mass% or less Ti, 0.5 mass% or less Nb, 1.0 mass% or less V, and 1.0 mass% or less W, the total amount of Nb, V, and W being 0.1 to 2.0 mass%, with the balance being Fe and impurities; As carbonitrides, Cr is 25 mass% or less, and the total amount of Nb, V and W is 10 mass% or less. Above Contains at least carbonitride and all of the carbonitrides have an average particle size of 5.0 μm or less. It is a martensitic stainless steel material having a metal structure.

[0009] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: The method for producing the martensitic stainless steel material comprises the steps of: a hot working step of heating a stainless steel having a composition containing 0.28 to 0.70 mass% C, 2.0 mass% or less Si, 2.0 mass% or less Mn, 10 to 17 mass% Cr, 3.0 mass% or less Mo, 0.008 to 0.40 mass% N, 0.1 mass% or less Ti, 0.5 mass% or less Nb, 1.0 mass% or less V, and 1.0 mass% or less W, the total amount of Nb, V, and W being 0.1 to 2.0 mass%, with the balance being Fe and impurities, to 1200°C or higher, and then hot working the stainless steel at a reduction in area of ​​90% or more to obtain a worked material; An annealing step of annealing the workpiece; A quenching process of quenching the annealed workpiece at 1050 to 1200 ° C.; A sub-zero treatment step of subjecting the quenched processed material to a sub-zero treatment; a tempering process in which the sub-zero treated processed material is tempered under conditions in which the LMP represented by the following formula (1) is 7000 to 17000; The present invention relates to a method for producing a martensitic stainless steel material, comprising the steps of: LMP = (t + 273) × (C + log tr) (1) In the formula, t is the heating temperature (°C), C is a material constant 20, and tr is the holding time (h) at the heating temperature.

[0010] Furthermore, the present invention relates to a slide member comprising the martensitic stainless steel material. Effect of the Invention

[0011] According to the present invention, it is possible to provide a martensitic stainless steel material having excellent corrosion wear resistance, a manufacturing method thereof, and a slide member. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention.

[0013] The martensitic stainless steel material according to an embodiment of the present invention contains C: 0.28 to 0.70% by mass, Si: 2.0% by mass or less, Mn: 2.0% by mass or less, Cr: 10 to 17% by mass, Mo: 3.0% by mass or less, N: 0.008 to 0.40% by mass, Ti: 0.1% by mass or less, Nb: 0.5% by mass or less, V: 1.0% by mass or less, W: 1.0% by mass or less, the total amount of Nb, V and W is 0.1 to 2.0% by mass, and the balance consists of Fe and impurities. Here, in this specification, "impurities" means components that are mixed in due to raw materials such as ores and scraps and various factors in the manufacturing process when industrially manufacturing the martensitic stainless steel material, and are allowed within a range that does not adversely affect the present invention. For example, impurities also include inevitable impurities. Specific examples of impurities include O: 0.01% by mass or less, P: 0.04% by mass or less, S: 0.40% by mass or less, Sn: 0.3% by mass or less, Ta: 0.1% by mass or less, REM: 0.01% by mass or less, Bi: 0.1% by mass or less, Pb: 0.1% by mass or less.

[0014] Further, the martensitic stainless steel material according to an embodiment of the present invention may further contain one or more selected from Ni: 0.05 to 2.0% by mass, Cu: 0.01 to 2.0% by mass, Al: 0.1% by mass or less. Further, the martensitic stainless steel material according to an embodiment of the present invention may further contain B: 0.1% by mass or less. Furthermore, the martensitic stainless steel material according to an embodiment of the present invention may further contain one or more selected from Ca: 0.02% by mass or less, Mg: 0.02% by mass or less, Zr: 0.02% by mass or less, Hf: 0.02% by mass or less, Co: 0.10% by mass or less.

[0015] <C: 0.28 to 0.70% by mass> C is an element necessary to obtain a martensitic structure (a structure in which the metal structure contains a martensite phase) by quenching treatment and to form carbonitrides. In order to sufficiently obtain this effect, the content of C is controlled to be 0.28% by mass or more, preferably 0.35% by mass or more. On the other hand, if the content of C is too high, the carbonitrides become excessively coarsened and the desired corrosion-resistant wear resistance cannot be obtained. Therefore, the content of C is controlled to be 0.70% by mass or less, preferably 0.55% by mass or less, more preferably 0.45% by mass or less. Here, in this specification, "carbonitride" means a compound in which carbon and / or nitrogen is combined with a metal element (for example, Cr, Nb, V, W, Ti, etc.). Note that carbides containing little nitrogen and nitrides containing little carbon also fall within the scope of "carbonitrides" in this specification.

[0016] <Si: 2.0% by mass or less> Si is an element effective for deoxidation, but excessive addition becomes a factor increasing the manufacturing cost. Therefore, the content of Si is controlled to be 2.0% by mass or less, preferably 0.8% by mass or less, more preferably 0.5% by mass or less. On the other hand, the lower limit of the content of Si is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, still more preferably 0.1% by mass or more.

[0017] <Mn: 2.0% by mass or less> Similar to Si, Mn is also an element effective for deoxidation, but excessive addition becomes a factor increasing the manufacturing cost. Therefore, the content of Mn is controlled to be 2.0% by mass or less, preferably 0.8% by mass or less, more preferably 0.5% by mass or less. On the other hand, the lower limit of the content of Mn is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, still more preferably 0.1% by mass or more.

[0018] <Cr: 10 - 17% by mass> Cr is an essential element for imparting corrosion resistance. Also, Cr is an element that forms carbonitrides and reduces corrosion-resistant wear resistance. Considering various environments including those containing salt, the Cr content is controlled to be 10 mass% or more, preferably 10.5 mass% or more. On the other hand, if the Cr content is too high, it becomes a factor increasing the manufacturing cost. Therefore, the Cr content is controlled to be 17 mass% or less, preferably 16 mass% or less, more preferably 15 mass% or less.

[0019] <Mo: 3.0 mass% or less> Mo is an element effective for improving the corrosion resistance of martensitic stainless steel materials. However, since Mo is expensive, if the Mo content is too high, it becomes a factor increasing the manufacturing cost. Therefore, the Mo content is controlled to be 3.0 mass% or less, preferably 2.8 mass% or less, more preferably 2.5 mass% or less. On the other hand, the lower limit of the Mo content is not particularly limited, but preferably 0.01 mass% or more, more preferably 0.03 mass% or more, still more preferably 0.05 mass% or more.

[0020] <N: 0.008 - 0.40 mass%> N is an element necessary for forming carbonitrides and improving corrosion-resistant wear resistance. If the N content is too high, the carbonitrides become excessively coarsened and the desired corrosion-resistant wear resistance cannot be obtained. Therefore, the N content is controlled to be 0.40 mass% or less, preferably 0.18 mass% or less. Also, excessive reduction of the N content leads to an increase in refining cost, so it is controlled to be 0.008 mass% or more, preferably 0.01 mass% or more.

[0021] <Ti: 0.1 mass% or less> Ti is an element that improves corrosion-resistant wear resistance by combining with C or N to form carbonitrides. If the Ti content is too high, the carbonitrides become excessively coarsened and the desired corrosion-resistant wear resistance cannot be obtained. Therefore, the Ti content is controlled to be 0.1 mass% or less, preferably 0.09 mass% or less. On the other hand, the lower limit of the Ti content is not particularly limited, but preferably 0.001 mass% or more, more preferably 0.005 mass% or more.

[0022] <Nb: 0.5 mass% or less> Nb is an element that improves corrosion and wear resistance by combining with C or N to form carbonitrides. If the content of Nb is too high, the carbonitrides will become excessively coarse and the desired corrosion and wear resistance cannot be obtained. Therefore, the content of Nb is controlled to be 0.5 mass% or less, preferably 0.45 mass% or less. On the other hand, the lower limit of the content of Nb is not particularly limited, but is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, and still more preferably 0.1 mass% or more.

[0023] <V: 1.0 mass% or less> V is an element that improves corrosion and wear resistance by combining with C or N to form carbonitrides. If the content of V is too high, the carbonitrides will become excessively coarse and the desired corrosion and wear resistance cannot be obtained. Therefore, the content of V is controlled to be 1.0 mass% or less, preferably 0.8 mass% or less, more preferably 0.5 mass% or less. On the other hand, the lower limit of the content of V is not particularly limited, but is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, and still more preferably 0.05 mass% or more.

[0024] <W: 1.0 mass% or less> W is an element that improves corrosion and wear resistance by combining with C or N to form carbonitrides. If the content of W is too high, the carbonitrides will become excessively coarse and the desired corrosion and wear resistance cannot be obtained. Therefore, the content of W is controlled to be 1.0 mass% or less, preferably 0.8 mass% or less, more preferably 0.5 mass% or less. On the other hand, the lower limit of the content of W is not particularly limited, but is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, and still more preferably 0.05 mass% or more.

[0025] <Total amount of Nb, V and W: 0.1 - 2.0 mass%> Nb, V, and W combine with C and N as described above to form carbonitrides. Although carbonitrides contribute to the improvement of corrosion and wear resistance, depending on the content of elements contained in the carbonitrides (particularly Cr, Nb, V, and W), sufficient corrosion and wear resistance may not be obtained. From the perspective of forming carbonitrides with excellent corrosion and wear resistance, the total amount of Nb, V, and W is controlled to be 0.1 to 2.0% by mass, preferably 0.2 to 2.0% by mass, and more preferably 0.3 to 1.5% by mass.

[0026] <Ni: 0.05 to 2.0% by mass> Ni is an element that contributes to the improvement of strength. From the perspective of obtaining the effect of Ni, the content of Ni is preferably controlled to be 0.05% by mass or more, and more preferably 0.06% by mass or more. However, if Ni is contained in excess, the manufacturing cost increases, and there is a risk that a retained austenite phase is generated during quenching and the toughness decreases. Therefore, the content of Ni is preferably controlled to be 2.0% by mass or less, more preferably 0.50% by mass or less, and even more preferably 0.30% by mass or less.

[0027] <Cu: 0.01 to 2.0% by mass> Cu is an element that contributes to the improvement of strength and corrosion resistance. From the perspective of obtaining the effect of Cu, the content of Cu is preferably controlled to be 0.01% by mass or more, and more preferably 0.02% by mass or more. On the other hand, if Cu is contained in excess, there is a risk that the toughness decreases. Therefore, the content of Cu is preferably controlled to be 2.0% by mass or less, more preferably 0.50% by mass or less, and even more preferably 0.20% by mass or less.

[0028] <Al: 0.1% by mass or less> Al is an element that is effective for deoxidation and improves oxidation resistance and corrosion resistance. In addition, Al also has the effect of improving wear resistance by increasing the cleanliness of inclusions. However, if Al is contained in excess, the improvement of oxidation resistance and corrosion resistance saturates, and AlN and Al-based oxides agglomerate and coarsen, causing noise during wear. Therefore, the content of Al is preferably controlled to 0.1% by mass or less, more preferably 0.080% by mass or less, and still more preferably 0.05% by mass or less. On the other hand, the lower limit of the content of Al is not particularly limited, but is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, and still more preferably 0.01% by mass or more.

[0029] <B: 0.1% by mass or less> B is an element that forms BN and improves wear resistance. However, if B is contained in excess, the hardenability is excessively improved and the toughness deteriorates. Therefore, the content of B is preferably controlled to 0.1% by mass or less, more preferably 0.0040% by mass or less. On the other hand, the lower limit of the content of B is not particularly limited, but is preferably 0.0002% by mass or more, more preferably 0.001% by mass or more.

[0030] <Ca: 0.02% by mass or less> Ca is an element that improves the hot workability of martensitic stainless steel. However, if Ca is contained in excess, the corrosion resistance deteriorates. Therefore, the content of Ca is preferably controlled to 0.02% by mass or less, more preferably 0.0050% by mass or less. On the other hand, the lower limit of the content of Ca is not particularly limited, but is preferably 0.0002% by mass or more, more preferably 0.0005% by mass or more.

[0031] <Mg: 0.02% by mass or less> Mg is an element that inevitably enters stainless steel produced using general refining methods. Also, if Mg is contained in excess, large and hard MgO is generated, which has an adverse effect on the grindability of martensitic stainless steel materials. Therefore, the Mg content is preferably controlled to 0.02 mass% or less, more preferably 0.0050 mass% or less. On the other hand, the lower limit of the Mg content is not particularly limited, but is preferably 0.0002 mass% or more, more preferably 0.0005 mass% or more.

[0032] <Zr: 0.02 mass% or less> Zr is an element that improves corrosion resistance and heat resistance. However, if Zr is contained in excess, it becomes a factor in increasing the manufacturing cost. Therefore, the Zr content is preferably controlled to 0.02 mass% or less, more preferably 0.0050 mass% or less. On the other hand, the lower limit of the Zr content is not particularly limited, but is preferably 0.0002 mass% or more, more preferably 0.0005 mass% or more.

[0033] <Hf: 0.02 mass% or less> Hf is an element that improves corrosion resistance and oxidation resistance at high temperatures. However, if Hf is contained in excess, it becomes a factor in increasing the manufacturing cost. Therefore, the Hf content is preferably controlled to 0.02 mass% or less, more preferably 0.0050 mass% or less. On the other hand, the lower limit of the Hf content is not particularly limited, but is preferably 0.0002 mass% or more, more preferably 0.0005 mass% or more.

[0034] <Co: 0.10 mass% or less> Co is an element that improves toughness and high-temperature corrosion resistance. However, if Co is contained in excess, it becomes a factor in increasing the manufacturing cost. Therefore, the Co content is preferably controlled to 0.10 mass% or less, more preferably 0.050 mass% or less. On the other hand, the lower limit of the Co content is not particularly limited, but is preferably 0.001 mass% or more, more preferably 0.003 mass% or more.

[0035] The martensitic stainless steel material according to the embodiment of the present invention has a metal structure containing carbonitrides. The carbonitride contains 25 mass % or less of Cr and 10 mass % or more in total of Nb, V and W. By controlling the contents to these values, it is possible to form carbonitrides having excellent corrosion and wear resistance. From the viewpoint of stably obtaining corrosion wear resistance by the carbonitride, the Cr content in the carbonitride is preferably 23 mass% or less, more preferably 20 mass% or less. On the other hand, the lower limit of the Cr content is not particularly limited, but is preferably 1 mass% or more, more preferably 3 mass% or more, and even more preferably 5 mass% or more. Also, the total amount of Nb, V and W in the carbonitride is preferably 15 mass% or more, more preferably 20 mass% or more. On the other hand, the upper limit of the total amount of Nb, V and W is not particularly limited, but is preferably 60 mass% or less, more preferably 50 mass% or less.

[0036] In this specification, the Cr content and the total amount of Nb, V and W in the carbonitrides are calculated by extracting the carbonitrides from the martensitic stainless steel material and analyzing them using a scanning electron microscope (SEM) and an energy dispersive X-ray analyzer (EDS). The carbonitrides can be extracted using the method described below.

[0037] The carbonitride has an average particle size of 5.0 μm or less. By controlling the average particle size within this range, corrosion wear resistance can be improved. The lower limit of the average particle size of the carbonitride is not particularly limited, but is preferably 0.1 μm or more, more preferably 0.3 μm or more, and even more preferably 0.5 μm or more. In this specification, the average grain size of carbonitrides means the average value of the equivalent circle diameter measured by observing a mirror-finished cross section of a martensitic stainless steel material with a Schottky scanning electron microscope. The equivalent circle diameter means the diameter of a circle having an area equal to the area of ​​the carbonitrides appearing on the observed surface.

[0038] The martensitic stainless steel material according to the embodiment of the present invention has a Vickers hardness of preferably 600HV or more, more preferably 650HV or more, and even more preferably 700HV or more. If the Vickers hardness is within such a range, the corrosion wear resistance can be improved. The upper limit of the Vickers hardness is not particularly limited, but is preferably 1000HV, more preferably 900HV, and even more preferably 800HV.

[0039] The martensitic stainless steel material according to the embodiment of the present invention may be in the form of a plate material or a wire material, but is preferably in the form of a wire material.

[0040] The martensitic stainless steel material according to the embodiment of the present invention can be manufactured in accordance with a method known in the art, except for melting stainless steel having the above composition. A typical manufacturing method for the martensitic stainless steel material according to the embodiment of the present invention includes a hot working step of heating stainless steel having the above composition and then hot working it to obtain a worked material, an annealing step of annealing the worked material, a quenching step of quenching the annealed worked material, a subzero treatment step of subzero treating the quenched worked material, and a tempering step of tempering the subzero treated worked material.

[0041] <Hot processing process> The hot working process is a process in which stainless steel having the above composition is melted, forged or cast, heated to 1200°C or higher, and hot worked with an area reduction rate of 90% or more to obtain a worked material. By setting the heating temperature at 1200° C. or higher, carbonitrides can be sufficiently dissolved and the heating (soaking) time can be shortened. The upper limit of the heating temperature is not particularly limited, but is preferably 1250° C. or lower. The heating time may be appropriately set depending on the heating temperature, and is not particularly limited. By setting the reduction rate to 90% or more, the deformation of the carbonitride is promoted and the segregation region can be reduced. From the viewpoint of obtaining finer carbonitride and uniform dispersion, the reduction rate is preferably 95% or more. The upper limit of the reduction rate is not particularly limited, but is preferably 99.9% or less, more preferably 99.8% or less.

[0042] <Annealing process> The annealing step is a step of annealing the worked material obtained in the hot working step. By performing annealing, carbonitrides can be precipitated. The annealing method is not particularly limited, but may be performed by heating to a predetermined annealing temperature and then slowly cooling. The annealing temperature is not particularly limited, but is preferably 800 to 950° C., and more preferably 820 to 900° C. The annealing time may be appropriately set depending on the annealing temperature, and is not particularly limited, but is generally 1 to 10 hours. The cooling rate of the slow cooling is not particularly limited, but is preferably 30° C. / h or less.

[0043] <Quenching process> The quenching process is a process in which the annealed workpiece is quenched at 1050 to 1200°C. By performing quenching, a martensite structure can be obtained. The quenching method is not particularly limited, but may be such that the annealed material is held at 1050 to 1200° C., preferably 1090 to 1150° C., and then rapidly cooled. If the quenching temperature is less than 1050°C, the amount of dissolved C is insufficient, resulting in reduced hardness, whereas if the quenching temperature exceeds 1200°C, the crystal grains become coarse, resulting in reduced toughness and the formation of excessive retained austenite. The holding time at the quenching temperature may be appropriately set depending on the quenching temperature, and is not particularly limited, but is generally 10 minutes to 2 hours. The quenching method is not particularly limited, but air cooling, water cooling, oil cooling, etc. can be used.

[0044] <Sub-zero treatment process> Sub-zero treatment is a process in which hardened workpieces are subjected to sub-zero treatment. By performing sub-zero treatment, the amount of austenite remaining after quenching (hereinafter referred to as "residual austenite") can be reduced. In other words, a part of the retained austenite is transformed into martensite, and the reduction in the amount of retained austenite can increase the hardness. The method of sub-zero treatment is not particularly limited, but may be such that the quenched processed material is held at a temperature of 0° C. or lower, preferably at a temperature of −77 to −196° C. For example, the quenched processed material may be immersed in liquid nitrogen (−196° C.) for a predetermined period of time. The retention time may be appropriately set depending on the temperature, and is not particularly limited, but is typically 30 minutes to 1 hour.

[0045] <Tempering process> The tempering process is a process for tempering the sub-zero treated processed material. Tempering can impart toughness to the martensite structure formed by the quenching and sub-zero treatment steps. The tempering step is carried out under conditions such that the LMP is 7,000 to 17,000, preferably 8,000 to 15,000. Here, LMP is the Larson-Miller parameter and is expressed by the following equation (1). LMP = (t + 273) × (C + log tr) (1) In the formula, t is the heating (tempering) temperature (°C), C is a material constant, and tr is the holding time (h) at the heating temperature. Note that the material constant C is around 20 for most heat-resistant steels. If the LMP is less than 7000, the recovery of toughness is insufficient, whereas if the LMP exceeds 17000, the hardness and the amount of retained austenite are reduced. A typical tempering process is carried out at a heating temperature of 120 to 300° C. for a holding time of 30 minutes to 2 hours.

[0046] The martensitic stainless steel material according to the embodiment of the present invention has excellent corrosion wear resistance. In addition, the martensitic stainless steel material according to the embodiment of the present invention also has excellent corrosion resistance. Therefore, the martensitic stainless steel material according to the embodiment of the present invention can be used in various applications requiring corrosion wear resistance and corrosion resistance. In particular, the martensitic stainless steel material according to the embodiment of the present invention is suitable for use in sliding members such as bearings. EXAMPLES

[0047] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these. <Experiment 1> 100 kg of stainless steel having the composition shown in Table 1 was melted in a vacuum melting furnace and cast into a Φ180 mm slab. Next, the slab was heated to 1230 ° C, hot worked to Φ10 mm (reduction of area 99.7%), and cooled to room temperature to obtain a wire (processed material). Next, the wire was annealed in a batch furnace at 850 ° C for 2 hours and slowly cooled. Next, the annealed wire was cut into a length of 100 mm, held at the quenching temperature shown in Table 2 for 10 minutes, and air-cooled to a temperature of 50 ° C or less. Next, the quenched wire was immersed in liquid nitrogen for 30 minutes to perform sub-zero treatment. Next, the tempering temperature was controlled to obtain the LMP shown in Table 2, and the tempering treatment was performed, followed by air cooling to obtain a test material (martensitic stainless steel material). In the tempering treatment, the holding time was set to 60 minutes, and the material constant C for calculating the LMP was set to 20.

[0048] [Table 1]

[0049] The test materials obtained above were subjected to the following evaluations.

[0050] (Composition of carbonitride) A test piece 5 mm long was cut out from the test material, and the entire surface was polished with #400. Then, electrolysis (constant voltage of 100 mV) was performed in a non-aqueous solution (10% by mass maleic anhydride + 2% by mass tetramethylammonium chloride + remaining methanol) to dissolve 1 g of the matrix. Next, the sample was filtered through a filter with a hole diameter of 0.2 μm to extract the residue. The obtained residue was dried on the filter and then identified with an X-ray diffraction device. As a result of the identification, no inclusions or oxides were detected, and it was confirmed that the residue was carbides and nitrides. The composition of the carbonitrides was determined by using a scanning electron microscope (SEM) and an energy dispersive X-ray analyzer (EDS) to randomly select five locations on the residue, determine the Cr, Nb, V and W contents by area analysis, and take the average value as the result.

[0051] (Average particle size of carbonitride) A test piece 10 mm long was cut from the test material, cut in half parallel to the rolling direction, and the cut surface was mirror-polished. Using a Schottky scanning electron microscope (SU5000, Hitachi High-Tech Corporation), the size (circle equivalent diameter) of the carbonitrides present in an observation area of ​​50 x 50 μm was measured in 10 fields of view. The method used was to capture images using automatic particle analysis, recognize the particles, and measure the size of the carbonitrides. The average particle size of the carbonitrides was calculated as the average value of the sizes of the carbonitrides measured in 10 fields of view.

[0052] (Vickers hardness) The Vickers hardness was measured using a Vickers hardness tester, by cutting test pieces from the test material and measuring the Vickers hardness in accordance with JIS Z2244:2009. The test force was 294.2 N. The Vickers hardness was measured at five random points, and the average value was used as the result.

[0053] (Corrosion and wear resistance test) Test pieces (pins) were cut out from the test material, and the corrosion wear resistance was evaluated using a pin-on-disk friction and wear tester. SUS440C (steel type M) was used for the disk. The pin-on-disk friction and wear test was performed at a sliding speed of 2.0 m / s, a load of 5.0 kgf, and for 30 minutes while dropping a 3 mass% NaCl solution. The height of the pin was measured before and after the test to determine the volume of the pin before and after the test, and the wear volume was calculated by subtracting the volume of the pin after the test from the volume of the pin before the test. The volume of the pin was calculated using the following formula (2). V=πr 2 h (2) In the formula, V is the volume of the test piece (pin) (mm 3 ), r is the radius of the test piece (mm), h is the height of the test piece (mm) In this evaluation, the pin wear volume was 20 mm 3 The following are ◎, 20mm 3 Over 30mm 3 The following are marked with an O, 30 mm 3 Anything exceeding this limit was judged as "X."

[0054] The results of the above evaluations are shown in Table 2.

[0055] [Table 2]

[0056] As shown in Table 2, Test Nos. 1 to 16 (invention examples) which satisfied the prescribed composition and had a metal structure containing the prescribed carbonitrides showed good results in the corrosion wear resistance test and the Vickers hardness evaluation. In contrast, Test Nos. 17 to 26 (Comparative Examples), which did not have the prescribed composition and metal structure, did not have sufficient evaluation results in the corrosion wear resistance test. Also, Test Nos. 24 and 26 did not have sufficient Vickers hardness.

[0057] <Experiment 2> In experiment 2, the heating temperature and area reduction rate in the hot working process, the quenching temperature and the tempering temperature were changed to carry out an experiment. Specifically, 100 kg of stainless steel of steel type A3 was melted in a vacuum melting furnace and cast into a Φ180 mm cast piece. Next, the cast piece was heated to the heating temperature shown in Table 3, and then hot worked to obtain the area reduction rate shown in Table 3, and cooled to room temperature to obtain a wire (processed material). Next, the wire was annealed at 850 ° C for 2 hours in a batch furnace and slowly cooled. Next, the annealed wire was cut into a length of 100 mm, held at the quenching temperature shown in Table 3 for 10 minutes, and air-cooled to a temperature of 50 ° C or less. Next, the quenched wire was immersed in liquid nitrogen for 30 minutes to perform sub-zero treatment. Next, the tempering temperature was controlled to obtain the LMP shown in Table 3, and the tempering treatment was carried out, followed by air cooling to obtain a test material (martensitic stainless steel material). In the tempering treatment, the holding time was set to 60 minutes, and the material constant C for calculating the LMP was set to 20.

[0058] The test materials obtained above were evaluated in the same manner as in Experiment 1. The results are shown in Table 3.

[0059] [Table 3]

[0060] As shown in Table 3, in Test Nos. 27 and 28 (examples of the present invention) which were hot worked with an area reduction rate of 90% or more, the average grain size of the carbonitrides was small and the evaluation results of the corrosion wear resistance test were good. In contrast, in Test Nos. 29 and 30 (Comparative Examples) which were hot worked with a reduction in area of ​​less than 90%, the average grain size of the carbonitrides was large, and the evaluation results of the corrosion wear resistance test were insufficient.

[0061] As can be seen from the above results, the present invention can provide a martensitic stainless steel material having excellent corrosion wear resistance, a manufacturing method thereof, and a slide member.

Claims

1. The composition includes C: 0.28 to 0.70 mass%, Si: 2.0 mass% or less, Mn: 2.0 mass% or less, Cr: 10 to 17 mass%, Mo: 3.0 mass% or less, N: 0.008 to 0.40 mass%, Ti: 0.1 mass% or less, Nb: 0.5 mass% or less, V: 1.0 mass% or less, and W: 1.0 mass% or less, the total amount of Nb, V, and W being 0.1 to 2.0 mass%, with the balance being Fe and impurities; A martensitic stainless steel material having a metal structure including at least carbonitrides having a Cr content of 25 mass% or less and a total amount of Nb, V and W of 10 mass% or more as carbonitrides, and the average grain size of all of the carbonitrides is 5.0 μm or less.

2. The martensitic stainless steel material according to claim 1, further comprising one or more selected from the group consisting of Ni: 0.05 to 2.0 mass%, Cu: 0.01 to 2.0 mass%, and Al: 0.1 mass% or less.

3. The martensitic stainless steel material according to claim 1 or 2, further comprising B: 0.1 mass% or less.

4. The martensitic stainless steel material according to any one of claims 1 to 3, further comprising one or more selected from the group consisting of Ca: 0.02 mass% or less, Mg: 0.02 mass% or less, Zr: 0.02 mass% or less, Hf: 0.02 mass% or less, and Co: 0.10 mass% or less.

5. The martensitic stainless steel material according to any one of claims 1 to 4, having a Vickers hardness of 600 HV or more.

6. The martensitic stainless steel material according to any one of claims 1 to 5, wherein the martensitic stainless steel material is a wire rod.

7. The martensitic stainless steel material according to any one of claims 1 to 6, which is used for a sliding member.

8. A method for producing the martensitic stainless steel material according to claim 1, comprising the steps of: a hot working step of heating a stainless steel having a composition containing 0.28 to 0.70 mass% C, 2.0 mass% or less Si, 2.0 mass% or less Mn, 10 to 17 mass% Cr, 3.0 mass% or less Mo, 0.008 to 0.40 mass% N, 0.1 mass% or less Ti, 0.5 mass% or less Nb, 1.0 mass% or less V, and 1.0 mass% or less W, the total amount of Nb, V, and W being 0.1 to 2.0 mass%, with the balance being Fe and impurities, to 1200°C or higher, and then hot working the stainless steel at a reduction in area of ​​90% or more to obtain a worked material; An annealing step of annealing the workpiece; a quenching step of quenching the annealed workpiece at 1050 to 1200 ° C; A sub-zero treatment step of subjecting the quenched processed material to a sub-zero treatment; a tempering process in which the sub-zero treated processed material is tempered under conditions in which the LMP represented by the following formula (1) is 7000 to 17000; A method for producing a martensitic stainless steel material, comprising: LMP=(t+273)×(C+log tr) (1) In the formula, t is the heating temperature (° C.), C is a material constant 20, and tr is the holding time (h) at the heating temperature.

9. A method for producing the martensitic stainless steel material according to claim 2, comprising the steps of: The method for producing a martensitic stainless steel material according to claim 8, wherein the stainless steel further contains one or more selected from Ni: 0.05 to 2.0 mass%, Cu: 0.01 to 2.0 mass%, and Al: 0.1 mass% or less.

10. A method for producing the martensitic stainless steel material according to claim 3, comprising the steps of: The method for producing a martensitic stainless steel material according to claim 8 or 9, wherein the stainless steel further contains B: 0.1 mass% or less.

11. A method for producing the martensitic stainless steel material according to claim 4, comprising the steps of: The stainless steel further contains one or more selected from Ca: 0.02 mass% or less, Mg: 0.02 mass% or less, Zr: 0.02 mass% or less, Hf: 0.02 mass% or less, and Co: 0.10 mass% or less. The method for producing a martensitic stainless steel material according to any one of claims 8 to 10.

12. A slide member comprising the martensitic stainless steel material according to any one of claims 1 to 7.

13. The slide member according to claim 12, wherein the slide member is a bearing.

Citation Information

Patent Citations

  • Rolling apparatus

    JP2003213380A

  • Pulley, pulley device with built-in clutch for engine auxiliary machine, and clearance structure between the pulley and the engine auxiliary machine

    JP2004340219A

  • Martensitic steel

    JP2007277639A

  • Ball bearing, and water pump and reel for fishing having the same

    JP2014055357A

  • Martensitic stainless steel component and manufacturing method therefor

    JP2020094275A